Comparative study of Uber and regular taxi service characteristics - Nistal, Patrick D.
Uber is a Transportation Network Company developed to connect passengers and drivers through a smartphone application. Despite the fact that Uber has grown and expanded internationally in the past 6 years, it faces legal and social issues more specifically an uproar among taxi drivers, operators, and gro ups due to the fact that it became the industry's disruptor. The main purpose of the study is to systematically differentiate Uber with the conventional taxi in terms of categories mainly classified under user perception. Uber will also be analyzed in comparison to existing ridesharing models. The user perception survey was conducted through online and hardcopy. The demographics, usage dynamics, service experience, and preferences ofrespondents were recorded. Descriptive statistics is mainly used in making simple summaries with the help of graphical representation Inferential statistics is used mainly to determine if two sample means are statistically different with the use of a Student's T -test through the Minitab 15 software. A Student's T-test is conducted in comparing answers by respondents who have not tried Uber and by respondents who have tried Uber. Ratings on multiple service aspects of Uber and the taxicab are also analyzed by the T-test. An analysis on the correlation of perceptions and demographics given by regular Uber users is also conducted.